STRATEGI PEMASARAN SEPEDA MOTOR BUKAN BARU PADA UD. DINA MOTOR DI KOTA BANGKINANG - M. Aminul Akbar; Samsurijal Hasan (Jurnal Riset Manajemen Indonesia, 2020)
This study aims to determine the strategy that should be carried out by UD. Dina Motor in Bangkinang City in marketing non-new motorbikes. The type of data used is primary data obtained through UD. Dina Motor Bangkinang City and secondary data in the form of documents, files and notes that have been published. Data collection techniques are interviews, FGD (Focus Group Discussion) and research files. Data analysis was carried out using SWOT analysis, which is mapping with strength maps, strengths, weaknesses, opportunities and threats to determine the factors of effective strategy advantage. The results showed that the map of the strength of the motorcycle marketing strategy is not new to UD. Dina Motor in Bangkinang City is in quadrant I as a market leader, namely a strategy to support aggressive growth (growth oriented strategy).